PENGARUH KONSUMSI BERITA DAN KOMUNIKASI POLITIK TERHADAP KETERLIBATAN WARGA NEGARA PADA MAHASISWA KOTA BANDUNG - Abidin, Muhammad Salman; Solihin; Nurdin, Iman Soleh; Maulana, Muhammad Yunus (JURNAL KEBANGSAAN RI, 2025)
This study aims to examine the effect of news consumption on citizen engagement through political communication mediation, using a quantitative approach and explanatory design. The main variables studied include news consumption (KBE), political communication (consisting of political issue concern/KIP and frequency of political communication/FKP), and citizen engagement as measured by citizen self-confidence (KDW), future involvement interest (MKM), and actions to promote important issues (MIP). Data were collected through an online survey involving 103 students in Bandung City. The analysis was conducted using Structural Equation Modeling based on Partial Least Squares (PLS-SEM) to evaluate direct and indirect relationships between variables. The results of the study showed that news consumption had a positive and significant effect on political issue concern (β = 0.460, p < 0.001) and frequency of political communication (β = 0.212, p = 0.007). Furthermore, political communication proved to be a significant mediator in bridging the influence of news consumption on citizen involvement. FKP had a positive effect on KDW (β = 0.382, p < 0.001) and MIP (β = 0.308, p < 0.001), while KDW was an important predictor for MKM (β = 0.522, p < 0.001) and MIP (β = 0.199, p = 0.007). Various indirect effect pathways also showed statistical significance, confirming the important role of political communication as a mediating mechanism. These findings underscore the importance of media literacy in increasing student political participation in the digital era.